THE EFFECT OF THE USE OF SERIES IMAGE MEDIA ON THE CREATIVE WRITING ABILITY OF STUDENTS OF GRADE IV MIN 9 MEDAN CITY - Adinda Nadda Namira; Zaini Dahlan (SOSIOEDUKASI, 2026)
This study aims to examine the effect of serial picture media on the creative writing ability of fourth-grade students at MIN 9 Kota Medan. This research employed a quasi-experimental method with a Nonequivalent Control Group Design involving 67 students: class IV-C as the experimental group (n = 34) and class IV-B as the control group (n = 33), selected through purposive sampling. Data were collected through pre-test and post-test using a creative writing rubric covering six aspects: story conformity, title writing, story structure, story elements, language use, and originality. Data were analyzed using descriptive and inferential statistics with SPSS version 25, including Shapiro-Wilk normality test, Levene's homogeneity test, and Independent Sample t-Test. The results showed that the mean post-test score of the experimental group (80.35) was significantly higher than the control group (73.55), with t = 2.218 and sig. = 0.030 (p < 0.05). These findings indicate that serial picture media has a significant positive effect on students' creative writing ability at MIN 9 Kota Medan.